Perancangan Alat Pengolahan Nira Aren Untuk Petani Nira Desa Kiarajangkung Kabupaten Tasikmalaya - Wijaya, Christopher; Tjandra, Sugih Sudharma; Herawati, Yani (Jurnal Rekayasa Sistem Industri, 2025)
Indonesia is an archipelagic country rich in biodiversity, including various types of plants that provide important natural resources for the people's basic and economic needs. One of these resources is Hasil Hutan Bukan Kayu (HHBK), such as brown sugar, which is produced from palm sap. The simple and basic palm sap processing method inspired this research to design processing tools that can improve product quality and efficiency for palm sap farmers in Kiarajangkung Village, Tasikmalaya Regency. The product design process began by conducting interviews to identify the farmers' needs. It was found that farmers needed three tools: a furnace for boiling palm sap, a pourer, and a palm sap mold. Specifications for these three processing tools were sought to meet the farmers needs using the House of Quality (HOQ) method. The next stage was concept generation, where six concepts were created for each of the three processing tools. Each concept was tested, and to narrow down the options, two concepts were chosen for the boiling furnace, three for the pourer, and three for the palm sap mold. From these, the best concept was selected and developed into a prototype. The processing tool prototype was designed using Solidworks software before being tested in real conditions. Next, a physical prototype was made, which was later tested by sap farmers. The prototype was tested using the functionality testing method. From the results of the prototype trials, it was found that the processing tool prototype successfully met several success indicators, with some refinements needed for the tools.